1988
DOI: 10.1021/bi00405a034
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the contribution made by the carboxylate group of an active site histidine-aspartate couple to binding and catalysis in lactate dehydrogenase

Abstract: The influence of aspartate-168 on the proton-donating and -accepting properties of histidine-195 (the active site acid/base catalyst in lactate dehydrogenase) was evaluated by use of site-directed mutagenesis to change the residue to asparagine and to alanine. Despite the fact that asparagine could form a hydrogen bond to histidine while alanine could not, the two mutant enzymes have closely similar catalytic and ligand-binding properties. Both bind pyruvate and its analogue (oxamate) 200 times more weakly tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
74
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 25 publications
9
74
0
Order By: Relevance
“…On the other hand, the reverse reaction requires unprotonated His (acting as a base) and the affinity for malate was not affected by the replacement of Asp by Ala or Asn. Similar results have been obtained by Clarke et al [23] who have used site-directed mutagenesis to study the contribution of Asp to the active site of a bacterial lactate dehydrogenase (the catalytic mechanism of which is assumed to be similar to that of malate dehydrogenases). They concluded that the formation of the ternary complex E-NADH-pyruvate was destabilized by the deletion of Asp but that the formation of E-NAD-lactate was not affected by the mutation since His was not positively charged in the oxidation of lactate.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…On the other hand, the reverse reaction requires unprotonated His (acting as a base) and the affinity for malate was not affected by the replacement of Asp by Ala or Asn. Similar results have been obtained by Clarke et al [23] who have used site-directed mutagenesis to study the contribution of Asp to the active site of a bacterial lactate dehydrogenase (the catalytic mechanism of which is assumed to be similar to that of malate dehydrogenases). They concluded that the formation of the ternary complex E-NADH-pyruvate was destabilized by the deletion of Asp but that the formation of E-NAD-lactate was not affected by the mutation since His was not positively charged in the oxidation of lactate.…”
Section: Discussionsupporting
confidence: 80%
“…However, for sorghum and D201N-mutated NADP-MDHs, no effect of the pH was observed in the pH range tested, which suggests that pK, of His229 is very high (> 9). Such a high value of pKd was predicted for NADP-MDH by Jackson et al [24], in contrast with cytosolic NAD-MDH [25] and bacterial lactate dehydrogenase [23] for which a pK, value of about 7 was determined. In contrast, k,,, of the D201A mutant seemed to be controlled by two ionisable groups.…”
Section: Discussionmentioning
confidence: 80%
“…This suggests a different mechanism for controlling substrate specificity compared with L-lactate dehydrogenase. The pH dependence of pyruvate K, in D-lactate dehydrogenase is in marked contrast to the situation found in L-lactate dehydrogenase, where pyruvate binds strictly to the protonated form of an activesite His195 which ionises in the binary complex with a pK, of about 7.5 (Clarke et al, 1988). This difference in pH dependence of pyruvate K, indicates that there is an alternative mechanism for substrate binding in D-lactate dehydrogenase compared with L-lactate dehydrogenase, which involves either a different ionisable group or a change in the environment of the active site histidine residue such that it has a perturbed pK,.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast, Bacillus stearothermophilus L-lactate dehydrogenase shows the reverse trend of a similar magnitude with a preference for 2-oxobutyrate (Hart et al, 1987) over oxalacetate (Clarke et al, 1987). It is relevant that the specificity of L-lactate dehydrogenase for oxalacetate can be enhanced considerably by engineering an arginine residue as a counter ion for the negatively charged carboxyl group (Clarke et al, 1988). Comparative analysis of substrate specificities of L-and D-lactate dehydrogenase suggests that the latter may have a positively charged amino acid residue in the vicinity of the active site which could interact with a negatively charged group at position C3 of the 2-0x0-acid substrate, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Site directed mutagenesis studies on LDH and mMDH indicate that both enzymes have a histidine located in the active site which interacts with an aspartate, and have proton-donating and accepting capabilities [17,18]. Furthermore, a…”
Section: Introductionmentioning
confidence: 99%